2018
DOI: 10.1093/icvts/ivy033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microribonucleic acids as potential biomarkers in the bicuspid aortic valve-associated aortopathy†

Abstract: Expression of circulating miR-17 and miR-106a in the BAV root phenotype patients correlates with the severity of aortopathy and the risk of adverse aortic events. MicroRNAs have the potential to serve as biomarkers in the BAV-associated aortopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Nevertheless, we found relevant differences in the microRNA expression patterns which might be valuable, considering even the limitations of our preliminary study. Inverse linear correlation between proximal aortic diameters and the CT values of circulating microRNAs have been described previously and linked to specific cellular pathways [9,21]. In accordance to these studies, we were able to confirm an inverse linear correlation between maximum aortic diameters and the values of circulating microRNA-17 and microRNA-20a in the pooled study population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, we found relevant differences in the microRNA expression patterns which might be valuable, considering even the limitations of our preliminary study. Inverse linear correlation between proximal aortic diameters and the CT values of circulating microRNAs have been described previously and linked to specific cellular pathways [9,21]. In accordance to these studies, we were able to confirm an inverse linear correlation between maximum aortic diameters and the values of circulating microRNA-17 and microRNA-20a in the pooled study population.…”
Section: Discussionsupporting
confidence: 89%
“…Young and predominantly male patients presenting with BAV regurgitation and concomitant aortic root dilatation demonstrate an increased prevalence of genetic abnormalities (i.e., TGFBR2, FBN1, NOTCH1, and SMAD2) [19,20]. As reported previously, such patients potentially have the most malignant aortopathy and, therefore, may present with the most extensive derangements in the microRNA expression [21]. To test this hypothesis, we examined the levels of circulating microRNA in the BAV root phenotype patients (i.e., BAV-AR subgroup) and compared them with other valvulo-aortic phenotypes of aortic valve lesions (i.e., BAV-AS and TAV-AS subgroups).…”
Section: Discussionmentioning
confidence: 60%
“…They found that the expression levels of circulating miR-122, miR-130a, and miR-486 were significantly associated with aortic valve morphology (i.e., bicuspid vs. tricuspid), whereas the downregulation of circulating miR-718 strongly correlated with the proximal aortic diameter and ascending aortic dilation. Our group found a significant downregulation of blood miR-17 and miR-106a in a BAV aortopathy cohort, as well as a strong correlation between aortic root size and blood levels of miR-17 and miR-106a in a pooled cohort of 96 BAV patients [20]. Furthermore, we focused specifically on those patients who underwent an isolated aortic valve surgery due to BAV and had a significant aortopathy progression during the postoperative follow-up (i.e., increase of ascending aortic diameter ≥ 3.0 mm).…”
Section: Circulating Micrornas and Bicuspid Aortopathymentioning
confidence: 52%
“…The variance may reflect differences in methodology or the known biological heterogeneity that makes BAV-TAA so difficult to study. This is reflected in a more recent study in which the expression of seven miRNAs was analysed according to distinct BAV phenotypic subgroups; those with aortic root dilatation and concomitant insufficiency versus BAV with severe aortic stenosis (Girdauskas et al 2018a). Within the root dilatation subgroup, circulating miR-17 and 106a were significantly increased in the less dilated (< 50 mm) compared to severely dilated (> 50 mm) aortas; however, when compared overall to the aortic stenosis cohort, significant differences were observed in all seven miRNAs (miR-17, miR-16a, miR19a, miR-20a, miR-21, miR-106a and miR-145) (Girdauskas et al 2018b).…”
Section: Circulating Mirnamentioning
confidence: 99%